Analyzing Genome-Wide Association Study Dataset Highlights Immune Pathways in Lip Bone Mineral Density - Liu, Xiaodong; Zhang, Yiwei; Tian, Jun; Gao, Feng (Frontiers in Genetics, 2020)
Abstract Osteoporosis is a common complex human disease. Until now, large-scale genome-wide association studies (GWAS) based on single genetic variant have reported some novel osteoporosis susceptibility variants. However, these risk variants only explain a small proportion of osteoporosis genetic risk, and most genetic risk is largely unknown. Interestingly, the pathway analysis method has been used in investigation of osteoporosis mechanisms and reported some novel pathways. Until now, it remains unclear whether there are other risk pathways involved in BMD. Here, we selected a lip BMD GWAS with 301,019 SNPs in 5,858 Europeans, and conducted a gene-based analysis (SET SCREEN TEST) and a pathway-based analysis (WebGestalt). On the gene level, BMD susceptibility genes reported by previous GWAS were identified to be the top 10 significant signals. On the pathway level, we identified 27 significant KEGG pathways. Three immune pathways including T cell receptor signaling pathway (hsa04660), Complement and coagulation cascades (hsa04610), and Intestinal immune network for IgA production (hsa04672) are ranked the top three significant signals. Evidence from the PubMed and Google Scholar databases further supports our findings. In summary, our findings provide complementary information to these nine risk pathways. We believe that our results advance our understanding of BMD mechanisms and will be very informative for future genetic studies in BMD.